Manajemen Kelas Dan Psikologi Belajar Sebagai Proses Pembelajaran Yang Kondusif - Wulandari, Dewi; Sunani, Eneng (LPPM STAI La Tansa Mashiro, 2025)
Classroom management is the skill of teachers as leaders and managers in creating a conducive classroom climate to achieve the success of teaching and learning activities in the classroom. Learning psychology is a discipline of psychology that contains psychological theories about learning, especially examining how individuals learn or carry out learning. In the teaching and learning process, classroom management and learning psychology as a way for the learning process to run conducively by doing this,: 1) teachers have the principles of classroom management learning activities (warm and enthusiastic, challenging, varied, flexible, emphasizing positive things, instilling self-discipline, attention, demonstration and concentration). 2) teachers have skills in classroom management, organizational skills, guiding and facilitating learning skills, skills in planning and implementing learning activities. 3) teachers are able to organize classrooms and creative and innovative teaching media. 4) teachers provide disciplinary guidance to students. 5) Development of communication by teachers and students in learning process activities. 6) teachers provide learning motivation to students.